1997
DOI: 10.1063/1.473470
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and decomposition of formic acid on MgO(001) surface as investigated by temperature programmed desorption and sum-frequency generation spectroscopy: Recurrence induced defect sites

Abstract: The change of the MgO(001) surface during the adsorption and thermal desorption of formic acid was investigated by temperature programmed desorption (TPD) and infrared-visible sum-frequency generation SFG spectroscopy. The TPD results revealed that the feature of desorption signals changed as the adsorption/thermal desorption process was repeated, despite no significant change of the low energy electron diffraction (LEED) pattern. The surface formate, produced by dissociative adsorption of formic acid, decompo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…The ZnO(1010) surface is a mixed ion‐terminated surface with an equal abundance of reactive three‐fold coordinated Zn and O sites. There is a clear difference in morphology along the two principal surface (0001) and (1120) directions, which makes it more complicated than, e.g., the well‐known MgO(001) surface 25, 26. Further, the (0001) direction lacks symmetry, making the ZnO(1010) surface more complicated than, for example, the much studied TiO 2 (110) surface 19, 27, 28.…”
Section: Resultsmentioning
confidence: 99%
“…The ZnO(1010) surface is a mixed ion‐terminated surface with an equal abundance of reactive three‐fold coordinated Zn and O sites. There is a clear difference in morphology along the two principal surface (0001) and (1120) directions, which makes it more complicated than, e.g., the well‐known MgO(001) surface 25, 26. Further, the (0001) direction lacks symmetry, making the ZnO(1010) surface more complicated than, for example, the much studied TiO 2 (110) surface 19, 27, 28.…”
Section: Resultsmentioning
confidence: 99%
“…9 One of the most intriguing possibilities for studying a reducible oxide is the role that oxygen defects play in the reaction of the oxide with reactants. The interaction between surface formates and oxygen vacancies has been studied on TiO 2 , 10,11 and the association of formates with oxygen vacancies has been proposed on MgO(001) 12 and ZrO 2 (100). 13 Dilara and Vohs used sputtering to induce oxygen defects in ZrO 2 and found that the CO : CO 2 product ratio increased with the occurrence of O vacancies.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of this kind can be extended to higher temperature investigation, to follow reaction intermediates in heterogeneous processes. 67 We note, in passing, that interesting vibrational studies of adsorption on a well-defined oxide surface [MgO(100) 68 and NiO (111) 69 ] have also been reported, underscoring the usefulness of the IR-visible SFG technique for a wide variety of surfaces.…”
Section: Sum Frequency Generationmentioning
confidence: 90%